2014
DOI: 10.1590/1413-78522014220300813
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic study of injuries in articular fractures of distal radius extremity

Abstract: OBJECTIVE: To analyze the incidence of wrist ligament and cartilage associated fractures of the distal radius, through arthroscopy, correlating with AO/ASIF classification. METHODS: Thirty patients aged between 20 and 50 years old, with closed fracture from groups B and C according to AO/ASIF classification were selected. All of them were submitted to wrist arthroscopy to address intra-articular injuries and reduction and osteosynthesis of the fracture. RESULTS: A high incidence of intra-articular injuries was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
6
0
4
Order By: Relevance
“…[50][51][52][53][54][55][56] Rates when diagnosed radiographically range from 13.3% to 29%. [57][58][59][60][61][62] Mudgal and Hastings suggest the mechanism of this combined injury can be attributed to a combination of tensile stress in ulnar deviation and axial (compression) stress in either radial or ulnar deviation.…”
Section: Special Case Scenario: Open Treatment Of Acute Scapholunate mentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52][53][54][55][56] Rates when diagnosed radiographically range from 13.3% to 29%. [57][58][59][60][61][62] Mudgal and Hastings suggest the mechanism of this combined injury can be attributed to a combination of tensile stress in ulnar deviation and axial (compression) stress in either radial or ulnar deviation.…”
Section: Special Case Scenario: Open Treatment Of Acute Scapholunate mentioning
confidence: 99%
“…63,64 Overall, intra-articular fractures are associated with higher rates of SL injury but SL injury can be found in extra-articular fractures as well. [50][51][52][53][54][57][58][59][60]62 Diagnosis of these concomitant injuries can be difficult. In 1997, Richards and colleagues 54 evaluated 118 distal radius fractures arthroscopically and found that 60% of patients with SL injury did not demonstrate an SL gap greater than 2 mm on radiographs.…”
Section: Special Case Scenario: Open Treatment Of Acute Scapholunate mentioning
confidence: 99%
“…Neuf études ont un suivi inférieur ou égal à 12 mois [7][8][9]17,[22][23][24][25][26]. Seules 2 études sont comparatives [4,7].…”
unclassified
“…D'autres études n'ont pas traité les lésions retrouvées [9,20,22]. Considérant la prise en charge, pour certains auteurs le brochage était systématique si une lésion était retrouvée, sans geste associé arthroscopique [4,11,23]. Une étude a réalisé une réparation à ciel ouvert des lésions stade 4 [24].…”
unclassified
See 1 more Smart Citation